Tindak Tutur Ilokusi Deddy Corbuzier Dengan Bintang Tamu Nadiem Makarim Dalam Podcast Close The Door - Monica Resti Febriani; Samsiarni; Febrina Riska Putri (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2023)
This study aims to describe the form of Deddy Corbuzier's illocutionary speech acts in his video podcast, so the focus of the problem related to this research is how Deddy Corbuzier's illocutionary speech acts are formed. The type of research used in this research is qualitative research using descriptive methods. The data in this study are illocutionary speech acts conveyed by Deddy Corbuzier in videos on his YouTube account. Based on the results of the study, it was found that in the utterances expressed by Deddy Corbuzier on his YouTube video content which was used as a data source, there were 32 forms of illocutionary speech acts, namely declaration, directive, expressive, representative, and commissive speech acts. The forms of speech acts that are often found in this study are expressive and representative speech acts.